Upper arm intermittent ischaemia reduces exercise-related increase of platelet reactivity in patients with obstructive coronary artery disease. Issue 16 (2nd June 2011) - Battipaglia, Irma; Scalone, Giancarla; Milo, Maria; Di Franco, Antonino; Lanza, Gaetano A; Crea, Filippo
Abstract : Objective: To assess whether upper arm ischaemia influences exercise-induced myocardial ischaemia and platelet activation in patients with coronary artery disease (CAD). Design: Crossover study. Setting: University hospital. Patients: Twenty patients (17 men) of mean±SD age 64±8 years with stable CAD. Interventions: Patients underwent two exercise stress tests (ESTs) on two separate days in a randomised manner: (1) a maximal EST only (EST-1); (2) a maximal EST after intermittent upper arm ischaemia (cycles of alternating 5-min inflation and 5-min deflation of a standard blood pressure cuff) (EST-2). Blood samples were obtained to evaluate platelet reactivity. Main outcome measures: Platelet reactivity was assessed by flow cytometry at rest and after EST, with and without ADP stimulation, by measuring the percentage of monocyte-platelet aggregates (MPAs) and CD41 platelet expression measured as mean fluorescence intensity. Results: Remote ischaemia had no significant effect on EST-induced myocardial ischaemia. At rest there were no differences before EST-1 and EST-2 in basal MPA (20.7±2.3 vs 20.8±2.4, p=0.56) and CD41 (21.5±2.3 vs 21.3±2.3, p=0.39), and ADP stimulation induced a similar increase in both MPA (+15.2±8.2% vs +14.9±8.4%, p=0.71) and CD41 (+15.7±5.7% vs 13.37±6.9%, p=0.59). While no differences in the increase in MPA and CD41 expression were observed after EST-1 and EST-2, ADP stimulation after EST-2 induced a lower increase in MPA (+18.3±8.1% vs +27.9±9.7%, p<0.001) and CD41 (+18.3±9.2% vs +27.2±12.4%, p<0.001) than after EST-1. Conclusion: These results show that, in patients with stable CAD, remote ischaemia induces protection against an exercise-related increase in platelet reactivity.